Perbandingan Hasil Belajar Peserta Didik Melalui Penggunaan Media Board Game The Mansion of Happiness dan Board Games Labirin - Hasanah, Uswatun; Ismail, Ilyas; Arif, Wiwin Pramita (Al-AHYA: Jurnal Pendidikan Biologi, 2023)
The aims of this study were: 1) To find out the learning outcomes of students who were taught using the Board Game the Mansion of Happiness media on the material for the reproduction system of class XI MIA Madrasah Aliyah Madani Alauddin. 2) Knowing the learning outcomes of students who were taught using the Labyrinth Board Game. 3) Knowing the significant differences in student learning outcomes between those who taught using the Board Game the Mansion of Happiness and the Labyrinth Board Game media. This study is quasi-experimental and used the Non-equivalent (Pretest-Posttest) Control Group Design. From the research, the score of student learning outcomes in the experimental class is in the high category with an average score in the first experimental class being 90 and in the second experiment is 86 In addition, the inferential analysis of the data on the one sample test showed that the significance value obtained was t-count 0.000 <0.05, in conclusion, there was a significant influence between the learning outcomes of students in experimental class 1 and experiment 2.